"Feeling fat, " disgust, guilt, and shame: Preliminary evaluation of a mediation model of binge-eating in adults with higher-weight bodies. (September 2022) - Anderson, Lisa M.; Hall, Leah M.J.; Crosby, Ross D.; Crow, Scott J.; Berg, Kelly C.; Durkin, Nora E.; Engel, Scott G.; Peterson, Carol B.
Abstract: "Feeling fat" is a subjective state that theoretically contributes to the maintenance of binge eating (BE). However, feeling fat, and its relation to BE among individuals with higher-weight bodies, has been infrequently studied. This study proposes a momentary-level model in which negative moral emotion states (disgust, guilt, shame) mediate the association between feeling fat and binge eating. In this study, 50 adults with higher-weight bodies ( M BMI =40.3 ± 8.5 kg/m 2 ; 84% female) completed a two-week ecological momentary assessment protocol, which measured experiences of feeling fat, emotion states, and binge-eating behavior. Univariate generalized linear mixed models (GLMM) evaluated the momentary associations among levels of feeling fat at Time 1, emotion states at Time 2, and binge eating at Time 2, controlling for Time 1 emotion states. GLMM results suggest that increases in each emotion from Time 1 to Time 2 mediated the association between Time 1 feeling fat and Time 2 binge eating. When modeled simultaneously within one multivariate multilevel structured equation model, disgust appeared to drive the relation between feeling fat and binge eating, over and above guilt and shame. Although preliminary, findings suggest increases in negative moral emotions, particularly disgust, mediate the feeling fat-binge eating association in adults with higher-weight bodies. Highlights: Momentary "feeling fat" relates to momentary guilt, shame, and disgust. "Feeling fat" may predict binge-eating episodes, via increased negative emotion. Disgust may drive the association between "feeling fat" and binge-eating episodes.